Social work education for the digital age: insight from information science. - Dali, Keren; Caidi, Nadia (Social Work Education, 2023)
This article presents an information science perspective on Social Work (SW) education based on the results of a comparative policy content evaluation (PCE) of accreditation documents in Canada and the U.S. It investigates to what extent information and technology education (ITE) is integral to the accreditation documents that guide the SW curriculum in both countries. Empirical results are presented in the context of current advances in information science, technology, and artificial intelligence affecting the practice of SW, social justice, and social change. With accreditation documents viewed as stage-setters for SW programs, it is proposed that technology- and information-driven change may not be reflected in the SW curriculum design in an adequate or timely fashion but is seen as a bonus, not essential knowledge. The article suggests some ways to revise the current accreditation documents and positions information science as a potential partner that can contribute to SW education.